Reciprocal Tariffs and the Fragility of Global Trade: Economic Impacts on Indonesia’s Palm Oil Sector - Suryantoro, Anton; Fitri Rukmana, Heristina; Gumelar Panghegar, Ganjar; Sjarief Sjaiful Nazli, Rizal (SocioHumania: Journal of Social Humanities Studies, 2025)
The implementation of a 32% reciprocal import tariff by the United States in April 2025, targeting Indonesian palm oil, reflects an intensifying global trend of trade protectionism. As one of Indonesia’s top export commodities, palm oil was severely affected by the policy, revealing the structural fragility of the country’s export-dependent economy. The tariff led to immediate disruptions in trade flows, price competitiveness, and employment across the palm oil supply chain. This study aims to analyze the economic impact of the U.S. tariff policy on Indonesia’s palm oil industry and to examine the government’s policy responses in mitigating these effects. The research also seeks to identify strategic lessons for improving trade resilience in the face of unilateral trade measures. The study adopts a qualitative descriptive approach, integrating macroeconomic analysis and international trade theory. It uses secondary data from trade statistics, government reports, and international institutions, combined with conceptual frameworks including global value chain theory, comparative advantage, and trade policy response models. The findings indicate that the tariff caused a 22.5% decline in export value and a 24.9% drop in volume within the first quarter after implementation. Approximately 17,000 workers were affected, and investor confidence weakened due to disruptions in downstream value chains. In response, the Indonesian government launched a five-pillar strategy covering trade diplomacy, market diversification, regulatory reform, fiscal support, and digital service trade bargaining. These findings highlight the urgent need for structural transformation, value-added industrial development, and adaptive trade governance to strengthen Indonesia’s long-term economic resilience.